A simulation model for forest fire spread: a contribution to support decision making regarding firefighting policies - Santos, Catarina Sintra dos (2022)
Forest fires are an increasingly frequent phenomenon in Portugal as well as worldwide. Understanding how they propagate is essential to extinguish or mitigate them more quickly and efficiently. The objective of this work is to study and model the way wildfire spreads assuming the forest as a graph, where the nodes correspond to forest stands and the arcs represent the path between them. To this end, algorithms were created in Python that allow for the simulation of the progression of fire in the graph, using mainly discrete event simulation models. This fire propagation takes into account several aspects of the forest, the wind being the most influential. Several experiments have been performed by changing both the fire ignition point, the wind direction and/or speed, or even the type of graph used. In the last experiments, firefighting means were also included in certain nodes in order to mitigate the fire spread and understand their impact in the behaviour of the fire.